If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -3y + 2z = 16 Solving x + -3y + 2z = 16 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3y' to each side of the equation. x + -3y + 3y + 2z = 16 + 3y Combine like terms: -3y + 3y = 0 x + 0 + 2z = 16 + 3y x + 2z = 16 + 3y Add '-2z' to each side of the equation. x + 2z + -2z = 16 + 3y + -2z Combine like terms: 2z + -2z = 0 x + 0 = 16 + 3y + -2z x = 16 + 3y + -2z Simplifying x = 16 + 3y + -2z
| 10+23-x=180 | | 8h+3(4h-6)= | | -1thirds=7 | | 7x+15=512x | | (-2n^3+8n^2+6)+(4n^3-7n^2)= | | -14x^2-50x+24= | | -2x+2x-5=-5 | | 12-21z= | | A+3a=12 | | 21/2+x+18=306 | | 10y=5x-6 | | -1/4+8= | | 3x(x+1)=12 | | 9d-28=4d-3 | | 9x-x^2=6 | | 8=5-7p^2+10p | | -2x+8=6-2X | | x*-3x-10=0 | | x+8=6-2x | | 3x-2y+3z=-4 | | (4n^3-4n)+(3n^3+7n+8)= | | 2x-y+z=-1 | | 17=-2*x+3 | | 3(7z-4)= | | 25k^2+30k+9=0 | | 125*5-25+10= | | (-3b^2-7b-4)+(7b^2+2b-4)= | | 4t+5+4t-7t=6+2 | | x^2(x^4+16)-8x=0 | | -5=5x^2-25x+25 | | log(6)(5x-3)=4 | | 25+2t=5(t+10) |